2021
DOI: 10.2196/26877
|View full text |Cite
|
Sign up to set email alerts
|

Utility, Value, and Benefits of Contemporary Personal Health Records: Integrative Review and Conceptual Synthesis

Abstract: Background Contemporary personal health record (PHR) technologies offer a useful platform for individuals to maintain a lifelong record of personally reported and clinically sourced data from various points of medical care. Objective This paper presents an integrative review and synthesis of the extant literature on PHRs. This review draws upon multiple lenses of analysis and deliberates value perspectives of PHRs at the product, consumer, and industry … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 96 publications
2
17
0
Order By: Relevance
“…Consequently, a patient's EHR data is often distributed among many providers that have none or poor data sharing among them [20]. Patient portals through which patients access the EHR data from their providers are empowering tools [17], however, they are traditionally tied to a single provider [19]. This makes it extremely challenging for the patients to aggregate the EHR data for obtaining a complete picture of their medical history and to make sense of it [16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, a patient's EHR data is often distributed among many providers that have none or poor data sharing among them [20]. Patient portals through which patients access the EHR data from their providers are empowering tools [17], however, they are traditionally tied to a single provider [19]. This makes it extremely challenging for the patients to aggregate the EHR data for obtaining a complete picture of their medical history and to make sense of it [16].…”
Section: Introductionmentioning
confidence: 99%
“…Literature has shown that patient portals like MyChart, My HealthVet, and My Health, brought benefits in the domains of consumer empowerment, patient engagement, and healthcare communication [17], and delivered a sense of trust in and improved collaboration with providers [19]. Patient portals have been able to enhance understanding of medical conditions, simplify and clarify patients' instructions, and provide a greater control over health outcomes, among others [17]. Similarly, they have played a key role in improving patient-provider communication and timely information sharing for clinical decisions [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consumer-centric technology, a PHR can be defined as “an electronic application through which individuals can access, manage, and share their health information and that of others for whom they are authorized, in a private, secure, and confidential environment” [ 6 ]. In this regard, PHR systems comprise information and communication technologies that can potentially help all types of end users maintain health and wellness [ 7 ], and specifically facilitate patients to manage their ongoing illnesses [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our review of the extant literature indicates that patients with chronic illnesses or disabilities, their caregivers, and people caring for older persons are more likely to adopt and use PHR technologies [ 15 , 44 - 46 , 58 - 61 ]. These groups of users will find PHR technologies useful as a communication tool to obtain personalized care from their clinicians [ 7 , 47 - 50 , 59 ] and as an organizational tool to help track patient health conditions, maintain medication lists, write patient diaries, and keep notes from physician consultations [ 7 , 8 , 41 , 49 , 50 , 60 , 62 ].…”
Section: Introductionmentioning
confidence: 99%